Changes to Some Physical Properties due to Conversion of Secondary Forest of Peat into Oil Palm Plantation - Heri Junedi; M Edi Armanto; Siti Masreah Bernas; Momon Sodik Imanudin (Sriwijaya Journal of Environment, 2017)
The purpose of this study was to study how the physical properties of peat change due to the conversion of secondary forest into oil palm plantations.  It was done by comparing the three conversion stages of the secondary forest into shrubs and oil palm plantations.  The study was conducted in Ogan Komering Ilir District, South Sumatera Province, about 100 km south of Palembang, Indonesia from August to December 2016.  Data collection was done randomly at all sites, each of five points for field sampling, observation of soil profile and measurement of hydraulic conductivity and water table depth.  The samples were collected at a depth of 0-30 cm, both for undisturbed cores and bulk samples.  The hydraulic conductivity was measured in the field using the auger holes method.  The peat strength was determined by using the hand operated cone penetrometer.  Data analysis was done descriptively and regression correlation test.  The results showed that conversion of secondary forests into oil palm plantations has led to the decline in the quality of some of the physical properties of peat by decreasing total porosity, water table depth, hydraulic conductivity, organic matter content, moisture content and increasing the bulk density and peat strength.